Diagnostic whole genome sequencing and split‐read mapping for nucleotide resolution breakpoint identification in CNTNAP2 deficiency syndrome. Issue 10 (16th July 2014) - Watson, Christopher M.; Crinnion, Laura A.; Tzika, Antigoni; Mills, Alison; Coates, Andrea; Pendlebury, Maria; Hewitt, Sarah; Harrison, Sally M.; Daly, Catherine; Roberts, Paul; Carr, Ian M.; Sheridan, Eamonn G.; et al.
ABSTRACT: Whole genome sequencing (WGS) has the potential to report on all types of genetic abnormality, thus converging diagnostic testing on a single methodology. Although WGS at sufficient depth for robust detection of point mutations is still some way from being affordable for diagnostic purposes, low‐coverage WGS is already an excellent method for detecting copy number variants ("CNVseq"). We report on a family in which individuals presented with a presumed autosomal recessive syndrome of severe intellectual disability and epilepsy. Array comparative genomic hybridization (CGH) analysis had revealed a homozygous deletion apparently lying within intron 3 of CNTNAP2 . Since this was too small for confirmation by FISH, CNVseq was used, refining the extent of this mutation to approximately 76.8 kb, encompassing CNTNAP2 exon 3 (an out‐of‐frame deletion). To characterize the precise breakpoints and provide a rapid molecular diagnostic test, we resequenced the CNVseq library at medium coverage and performed split read mapping. This yielded information for a multiplex polymerase chain reaction (PCR) assay, used for cascade screening and/or prenatal diagnosis in this family. This example demonstrates a rapid, low‐cost approach to converting molecular cytogenetic findings into robust PCR‐based tests. © 2014 The Authors. American Journal of Medical Genetics Part A Published by Wiley Periodicals, Inc.